The Effect Of Adversity Quotient On Entrepreneurial Motivation - Reni Respita (Unversitas Muhammadiyah Mataram, 2021)
Abstract :This study aims to analyze the effect of the Adversity Quotient on students' entrepreneurial motivation at the Faculty of Economics, Padang State University. The total population is 1,209 students. Samples were taken using proportional random sampling technique with a sample of 300 students. In collecting data, a questionnaire was used as a technique for collecting it. Simple regression analysis is a data analysis technique used with the help of the SPSS 16 program. Based on the data analysis, it can be concluded that the adversity quotient has a positive and significant effect in increasing student entrepreneurial motivationAbstrak:Penelitian ini bertujuan untuk menganalisis efekAdversity Quotientterhadap motivasi berwirausaha mahasiswa di fakultas ekonomi Universitas Negeri Padang. Jumlah populasi adalah 1.209 orang mahasiswa. Sampel diambil dengan menggunakan teknik proportional random samplingdengan sampel berjumlah300 orang mahasiswa. Dalam pengumpulan data digunakan angket sebagai teknik pengumulannya. Analisis regresi sederhana merupakan teknik analisis data yang dipakai dengan bantuan program SPSS 16. Berdasarkan analisis data didapatkan kesimpulan bahwa adversity quotient memiliki pengaruh yang positif dan signifikan dalam meningkatkan motivasi berwirausaha mahasiswa.